Α-Cyperone inhibitory effects on tumor-derived DNA trigger microglia by STING pathway. (10th January 2021) - Gao, Peng; Ding, Ning; Lv, Jiaxin; Ramzan, Muhammad Noman; Wen, Qingping
Abstract: Ethnopharmacological relevance: Cyperus rotundus L. (Cyperaceae) is a widespread herbal in China and widely used in Traditional Chinese Medicine for multiple effects such as anti-arthritic, anti-genotoxic, anti-mutagenic, anti-bacterial effects, and analgesic. α-Cyperone is an active compound in Cyperus rotundus and has analgesic effects, but the exact molecular mechanisms require further investigations. Materials and methods: Tumor-derived DNA isolated from Lewis cell lines was transfected into microglia, and analyzed for stimulator of interferon genes (STING) effects. The downstream protein, such as interferon regulatory factor 3 (IRF3) and p65 nuclear factor–κB (NF-κB) were treated with STING siRNA and 5, 6-dimethyllxanthenone-4-acetic acid (DMXAA) in microglia. The α-Cyperone effect on microglia was also investigated. Results: Tumor-derived DNA activate microglia by upregulation of STING and downstream proteins. STING siRNA was reduced to its downstream expression and neuroinflammation inhibition was caused by tumor-derived DNA. However, DMXAA reversed the STING siRNA effect and increased neuroinflammation. α-Cyperone takes inhibitory effects on tumor-derived DNA that trigger microglia by STING pathway. Conclusions: α-Cyperone inhibition by tumor-derived DNA activated microglial to neuroinflammation in STING signaling pathway. Graphical abstract: Image 1